Tinjauan Kriminologi Budaya dalam Kasus Kekerasan dalam Rumah Tangga Sebagai Akibat dari Pernikahan Dini di Desa “X” Kabupaten Lombok Timur - Rafi Anorawi; Muhammad Zaky (JURNAL MANAJEMEN PENDIDIKAN DAN ILMU SOSIAL, 2024)
Research on cultural criminology in cases of domestic violence due to early marriage involves a careful analysis of the cultural elements that influence the level of violence in a domestic setting, especially in situations where marriage occurs at an early age. This research will use qualitative methods with data collection techniques through interviews with related parties, observation, and literature study. Researchers aim to find out problems related to criminogenic culture in the form of early marriage that can trigger domestic violence. The collected data were analyzed using a criminological cultural theory approach to determine the criminogenic culture in the form of early marriage that can trigger domestic violence. The results of this study are expected to provide a new perspective to formulate more effective policies and interventions to protect individuals involved in early marriage from the risk of domestic violence.